High stakes: the rising cost of America's gambling addiction - Skolnik, Sam (Beacon Press, 2011)
Examines the impact of legalized gambling on American culture, describing the appeal of legalized gambling as a tool for politicians to raise revenues and create jobs, discussing a rise in gambling addictions, and explaining how gambling addiction can lead to higher indebtedness and increased amounts of divorces, suicides, and gambling-related crime